The impact of community children's playgrounds on neighborhood interactions and residents' mental health from an all-age sharing perspective - Jin, Yilin; Wang, Yuetong; Sun, Ning; Chen, Linquan; Zheng, Zhenhua (Frontiers in Public Health, 2025)
BackgroundThe outbreak of COVID-19 and rapid urbanization in China have put mental health at the forefront of societal concerns. Despite extensive studies on how community environments influence residents' mental health, the mechanisms underlying how community children's playgrounds within community environments influence residents' mental health across different age groups remain insufficiently studied.MethodsThe study is based on 1,159 questionnaire survey data from 14 districts in Shanghai in 2022. Descriptive statistics and structural equation modeling are used for the statistical analysis of the data.ResultsThe findings reveal variations in the mental health status of Shanghai residents across different ages, with depression rates being higher in the young and middle-aged groups than in the older adult groups. Moreover, there are differences in the influence of community children's playgrounds on the mental health of residents across different age groups. Community children's playground influences the mental health of residents in the young adult and middle-aged groups, while neighborhood interaction has a more pronounced influence on the mental health of middle aged and older adult groups. The influence of children's playgrounds on children's mental health is more realized through the intermediary role of neighborhood communication, and the influence on the mental health of the older adult is completely realized through the intermediary role of neighborhood communication.ConclusionIn future community planning, renovation, and development, it is essential not only to meet the distinct needs of various age groups but also to pay more attention to the needs of young adults to enhance their mental health and ultimately improve the mental health of all residents.